1998
DOI: 10.1149/1.1838828
|View full text |Cite
|
Sign up to set email alerts
|

Methanol Tolerant Oxygen Reduction Catalysts Based on Transition Metal Sulfides

Abstract: The oxygen reduction activity and methanol tolerance of a range of transition metal sulfide electrocatalysts have been evaluated in half-cell experiments and in a liquid-feed solid polymer electrolyte direct methanol fuel cell. These catalysts were prepared in high surface area form by direct synthesis onto various surface-functionalized carbon blacks. Of the materials tested, mixed-metal catalysts based on ReRuS and MoRuS were observed to give the best oxygen reduction activities. In addition, significant inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(81 citation statements)
references
References 2 publications
0
78
0
Order By: Relevance
“…Metal chalcogenides are known to exhibit significant oxygen reduction capability. At the same time it is found that these materials are inactive towards methanol [10][11][12][13]. Here we report the activity of a methanol tolerant carbon supported RuSe catalyst for oxygen reduction.…”
Section: Introductionmentioning
confidence: 71%
“…Metal chalcogenides are known to exhibit significant oxygen reduction capability. At the same time it is found that these materials are inactive towards methanol [10][11][12][13]. Here we report the activity of a methanol tolerant carbon supported RuSe catalyst for oxygen reduction.…”
Section: Introductionmentioning
confidence: 71%
“…Being similar as the oxides, transition metal nitrides [43][44][45] and sulfides [46] also show catalytic activity towards the ORR and OER in Li-air batteries. It is shown that these catalysts not only reduce the over-potentials, but also enhance battery's energy efficiency and lifespan by reducing or eliminating the electrolyte decomposition.…”
Section: Transition Metal Oxides Nitrides and Sulfidesmentioning
confidence: 93%
“…The cathode catalyst can be modified so that it is not active for MOR or poisoned by CO, thus decreasing the cathode depolarization and increasing the ORR activity (like nitrogen-modified carbon materials (Publication III), Fe porphyrins [28] or transition metal sulfides [29]. A large effort has been directed in designing new membrane materials that would have high conductivity with good mechanical stability and selectivity toward water and protons [18].…”
Section: Methanol Crossover In Dmfcmentioning
confidence: 99%